ISLAMIC EDUCATION AS A MEANING TO DEVELOP THE CONCEPT OF HUMANISM - Hakim, Alif Lukmanul (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Humanism is a concept that has an essence that assumes that humans have potential that can be developed. This paper aims to analyze the essence of Islamic Education as a means to develop the concept of humanism which is correlated with Islamic teachings. This research uses a qualitative method and takes the form of library research that traces various sources of literature, books, and scientific journals related to the concept of humanism and Islamic education. The results of this study reveal that the concept of humanism is in harmony with Islamic education. This relevance includes that humans are born in a state of nature, interpret humans as beings who have potential that can be developed, and are egalitarian to every human being. Islamic educational institutions have a big role and responsibility in carrying out the concept of humanism which is assisted by family, environment, and social community.